Kerangka Epistemologi Ilmu dalam Psikologi Islam - Rahmad Salahuddin (Universitas Muhammadiyah Sidoarjo, 2020)
This research aims to find out Islamic Psychology as a new school of psychology, to provide a new path for scientists that the view of humans is not only based on philosophical speculation, and human observation is only on the aspect of self that appears, as in the observation of psychoanalysis, humanistic, and cognitive psychology, but views humans as part of the creator ( hi min ). The research method used is the study of literature on sources that explain how Islamic Psychology as a new school in the field of psychology. Therefore, to achieve the validity in the knowledge of science, epistemology building is needed which presents various approaches in analyzing the sources of knowledge. This is known as Quasi-Scientific which presents three patterns of approach in studying the sources of inter-infantile, and knowledge. This article provides an argument about the use of three patterns of approach in studying humans as a source of knowledge, so as to prove the validity of Islamic psychology